Rehydration of air dried oral smears using honey - V, Subashini; Ramani, Pratibha; ., Mpbrundha; N, Anuja; J Sherlin, Herald; .S, Gheena; R, Abhilasha; Jayaraj, Giffrina (International Journal of Dental Research, 2018)
Background: Papanicolaou stains, very reliable cytological staining in diagnosis of oral carcinoma. In routine practice, 95% ethanol is used to fix the slides while preparing for Pap smears. The problems associated with pap smear such as short of supply and storage of alcohol, wet fixing of slides and transporting them to the cytology centre if the Pap smears are prepared at a peripheral centre. If an alternative method of rehydrating the air-dried oral smears is known we can overcome these problems. Until the date only few studies regarding rehydration of oral smears as a substitute for wet fixation.Aim: The aim of this study is to use honey as an alternative for rehydrating air dried oral smears.Material and methods: This study was done over than 3 months. Two sets of oral smears wet and air dried ,Overall 40 smears were examined; The first set were fixed in 95% ethyl alcohol. The other set of smears were air dried and rehydrated with honey solution(2 parts honey and 1 part saline)Both the smears were stained with Pap stain, examined for preservation of cytomorphological features and evaluated by two experienced pathologists using the light microscope.Results and analysis: This study revealed that immersion of air dried PAP smears in honey for 30 minutes is effectively same as wet smear which is routine methodConclusion: Rehydration, followed by fixation of air-dried smears, is a simple, feasible, applicable and reliable fixation technique, which is comparable to the wet-fixed conventional technique, used for oral smears and can be applied for evaluation on a routine basis.